FOUNDATIONS OF TEACHING READING IN ENGLISH THROUGH THE PHONETIC METHOD WITHIN THE MONTESSORI FRAMEWORK (KONFERENSIYA, 2025)
This article explores the application of the phonetic principle, acornerstone of language instruction within the globally esteemed and results-provenMontessori methodology. The study details specific techniques for teaching alphabetrecognition and word decoding within the Montessori approach to effectivelyfacilitate English reading acquisition. Particular emphasis is placed on instructionalmethods utilizing phonetic segmentation models, including VC (Vowel-Consonant)and CVC (Consonant-Vowel-Consonant) patterns. The article argues that thisstructured phonetic foundation, aligned with the child’s developmental stages, fostersrapid development of phonemic awareness, independent reading skills, and a solidbase for vocabulary expansion and advanced language competencies